Dietary rosemary oil alleviates heat stress-induced structural and functional damage through lipid peroxidation in the testes of growing Japanese quail - Türk, Gaffari; Çeribaşı, Ali Osman; Şimşek, Ülkü Gülcihan; Çeribaşı, Songül; Güvenç, Mehmet; Çiftçi, Mehmet; Sönmez, Mustafa; Yüce, Abdurrauf; Bayrakdar, Ali; Yaman, Mine; Tonbak, Fadime; Kaya, Şeyma Özer (My University, 2016)
Supplementation of natural antioxidants to diets of male poultry has been reported to be effective in reducing or completely eliminating heat stress (HS)-induced reproductive failures. In this study, the aim is to investigate whether rosemary oil (RO) has a protective effect on HS-induced damage in spermatozoa production, testicular histologic structures, apoptosis, and androgenic receptor (AR) through lipid peroxidation mechanisms in growing Japanese quail. Male chicks (n = 90) at 15-days of age were assigned to two groups. The first group (n = 45) was kept in a thermo-neutral (TN) room at 22?C for 24 h/d. The second group (n = 45) was kept in a room with a greater ambient temperature of 34?C for 8 h/d (from 9:00 AM to 5:00 PM) and 22?C for 16 h/d. Animals in each of these two groups were randomly assigned to three subgroups (RO groups: 0, 125, 250 ppm), consisting of 15 chicks (six treatment groups in 2 × 3 factorial design). Each of subgroups was replicated three times with each replicate including five chicks. The HS treatment significantly reduced the testicular spermatogenic cell counts, amount of testicular Bcl-2 (anti-apoptotic marker) and amount of AR. In addition, it significantly increased testicular lipid peroxidation, Bax (apop-totic marker) immunopositive staining, and the Bax/Bcl-2 ratio in conjunction with some histopathologic damage. Dietary supplementation of RO to diets of quail where the HS treatment was imposed alleviated HS-induced almost all negative changes such as increased testicular lipid peroxidation, decreased numbers of spermatogenic cells, and decreased amounts of Bcl-2 and AR, increased ratio of Bax/Bcl-2 and some testicular histopathologic lesion. In conclusion, dietary supplementation of RO for growing male Japanese quail reared in HS environmental conditions alleviates the HS-induced structural and functional damage by providing a decrease in lipid peroxidation.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Rosemary oil; Heat stress; Spermatogenic cell; Testis; Quail